2014
DOI: 10.1007/s11605-014-2571-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Early Surgery for Chronic Pancreatitis: Impact on Pain, Pancreatic Function, and Re-intervention

Abstract: Data from this study supports considering early surgery for pain management in patients with chronic pancreatitis, with the potential of a reduced risk of pancreatic insufficiency and the need for further intervention. Further prospective randomized studies are warranted comparing early surgery against conservative step-up approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 32 publications
1
50
0
8
Order By: Relevance
“…If medical treatment is ineffective within a given, limited time period, or if endoscopic and/or surgical therapy are indicated, these more invasive treatments should not be unduly delayed in hopes of “spontaneous” pain relief over time (119). Patients who have failed or refused endoscopic or surgical therapy should be continued on the most effective medical approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If medical treatment is ineffective within a given, limited time period, or if endoscopic and/or surgical therapy are indicated, these more invasive treatments should not be unduly delayed in hopes of “spontaneous” pain relief over time (119). Patients who have failed or refused endoscopic or surgical therapy should be continued on the most effective medical approaches.…”
Section: Resultsmentioning
confidence: 99%
“…However, some patients may decline surgery, are too high risk for surgery or may improve sufficiently following initial endoscopic therapy to not require a definitive surgical approach (11). If patients do not significantly improve following endoscopic therapy and they are surgical candidates, then surgical treatment should not be delayed (119). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, multiple studies have suggested that early surgery is superior in providing pain relief and improvement of quality of life, compared to the step-up approach in which medical therapy is followed by endoscopy and finally surgery [4-6]. Delaying invasive treatment such as surgery was negatively associated in an observational study, with the duration of pre-operative opioid use, multiple endoscopic interventions and the duration of chronic pancreatitis [4].…”
Section: Timing Of Surgery In Chronic Pancreatitismentioning
confidence: 99%
“…Sometimes as a last resort, surgical drainage and/or resection procedures are proposed in the case endoscopy fails. In the recent years increasing evidence tested the step-up approach, and multiple studies suggest the superiority of surgery compared to conservative and endoscopic measures [4-6]. This article describes the indications and different surgical procedures in chronic pancreatitis and puts focus on the timing of surgery in relation to other treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Even though studies have compared, endoscopy and surgery (8) no placebo-controlled studies have been performed and this question the effect of invasive treatments. Surgery has been stated to be the most effective treatment of pain in CP, and recent studies suggest early surgery for CP may even increase the likelihood of complete postoperative long-term pain relief (61). As anexample total pancreatectomy with islet cell transplantation is an emerging approach to treat patients with pancreatic pain.…”
Section: Theoretical Framework For Treatmentmentioning
confidence: 99%